Ethnicity and gender differences in risk, ambiguity attitude - Debosree Banerjee (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
We analyze gender difference in risk and ambiguity attitude of subjects across two different ethnicities that differ in the degree of female empowerment. Santal is a patriarchal tribe and Khasi is a matrilineal tribe with men and women being the social head in their respective societies. We compare subject's willingness to take up risk and ambiguity for themselves and on behalf of others. Besides we analyze the differences in risk and ambiguity attitude of subjects from these societies. Our findings show that women in both societies are significantly more risk averse, but not ambiguity averse. Patriarchal male and female are more risk averse in group risk than in individual risk but matrilineal subjects are not. Therefore, higher risk aversion in group is an ethnic trait among Santals. Comparing the between ethnicity differences we find that matrilineal subjects are more risk averse than patriarchal subjects. Regarding attitudes towards ambiguity, we did not find any gender or ethnicity differences.
Keywords: C93; D81; J15; J16; 330; Risk and Ambiguity; Gender; Matrilineal and Patriarchal society; Field experiment